History as art, art as history contemporary art and social studies education - Desai, Dipti; Hamlin, Jessica; Mattson, Rachel (The Teaching/Learning social justice series, 2010)
This textbook pioneers methods for using contemporary works of art in the social studies and art classroom to enhance an understanding of visual culture and history. The interdisciplinary teaching tookit provides a pedagogical resource - complete with theoretical background and practical suggestions for teaching &.S. history topics through close readings of both primary sources and provocative works of contemporary art--Publisher.